Design and Analysis of a Parallel Elastic Shoulder Joint for Humanoid Robotics Application - Sharafatdin Yessirkepov; Timur Umurzakov; Michele Folgheraiter (IEEE Access)
This paper presents an innovative hybrid cable-driven shoulder joint for humanoid robotics application. A blend of a flexible central limb and three rigid lateral limbs, form a 2-degree-of-freedom (2 DOF) mechanism that connects the mobile platform to the fixed base. This design leverages both good mechanical stability and the integration of an elastic element, which mitigates vibrations up to 40% and allows the storage and release of elastic potential energy up to $1.9 \,J$ . Initially, three alternative and incremental shoulder joint designs are presented and evaluated across two distinct experiments: 1) Energy storage analysis of the parallel mechanism during single cable motion and 2) Dynamic response and vibration damping. Following these experiments, a detailed analysis is performed on the stiffness properties of the proposed prototype, as it outperforms the other two designs. The dimension of the central elastic limb, made out of Thermo-Plastic Polyurethane (TPU), is optimized using Finite Element Analysis (FEA). The kinematic behavior of the proposed mechanism is approximated as a combination of linkages equipped with two universal joints, and its motion evaluated through numerical simulations and real experiments.